SISTEM INFORMASI AKUNTANSI KERUGIAN PIUTANG DENGAN METODE UMUR PIUTANG DAN ANALISA PERPUTARAN PIUTANG BERBASIS CLIENT SERVER (STUDI : PT BANK PEMBIAYAAN RAKYAT SYARIAH SURIYAH KANCAB SEMARANG) - Feni Mustika Sari (STEKOM PRESS, 2018)
Banking companies engaged in deposits in the form of time deposits, savings, and other forms equivalent to that and funds channeling funds as BPR businesses. As a finance company, it is demanded to be able to meet the needs of its customers, especially in providing credit or financing loans. PT Bank Rakyat Syariah Syariah Suriyah is seen experiencing an increase in loans or financing, but it is also followed by a decrease in the value of accounts receivable turnover, so that the efficiency of receivables collection is increasingly reduced. This will certainly be better if the company can reduce its receivables until the accounts receivable turnover can rise. PT Bank Rakyat Syariah Syariah Suriyah in managing the recording of accounts receivable is still done manually has not been automated so that with this system the recording of accounts receivable takes a long time because it still uses books - especially to record receivables when they occur, the numbers recorded are sometimes wrong. The availability of a computer has not been used optimally because the application used for accounts receivable problems is currently only an office application where there is no integration between one data with another data, especially for managing accounts receivable and the application used is Microsoft Office Excel. To resolve the existing problems, the authors propose an accounting system for accounts receivable loss with the method of age of accounts receivable and analysis of accounts receivable turnover at BPR Suriyah which will facilitate the management of accounts receivable data. The program is expected to be able to deal with existing problems.